Determination of the Dielectric Constant and the Thickness of Polymer Thin Film Based on SPR Curve - Hendro Hendro; R Hidayat; D Kurnia (Jurnal Otomasi Kontrol dan Instrumentasi, 2011)
The SPR curve fitting using the Winspall simulator to determine the dielectric constant and the thickness of MEH-PPV film is presented. Experiment was performed by measuring the SPR curve of gold layer and gold/MEH-PPV layers based on Kretschmann configuration. First, the dielectric constant and the thickness of gold film are determined by fitting the SPR curve. And then the dielectric constant and the thickness of MEH-PPV are determined by fitting its SPR curve. The thickness result calculation from curve fitting for MEH-PPV shows comparable to the result from SEM. This method makes Winspall program as a simple tool in analysis and calculation to determine dielectric constant and thickness, layer by layer in deposition. Keywords:dielectric constant, MEH-PPV, SPR, Winspall, curve fitting, thickness